The Effectiveness of the Student Facilitator and Explaining Learning Model in Improving Students' Learning Engagement in Islamic Religious Education - Arum Nuzulur Rohmah; Rosidi Rido; Abdul Aziz (At Turots: Jurnal Pendidikan Islam, 2026)
The Islamic Religious Education (PAI) learning process is often dominated by conventional teacher-centered methods, resulting in low student engagement and activeness in the classroom. To address this problem, an innovative learning model is needed that shifts the focus of learning to the students (student-centered), one of which is the Student Facilitator and Explainer (SFAE) model. This study aims to analyze and identify the effectiveness of implementing the SFAE learning model in increasing student learning activeness, specifically in Islamic Religious Education. This study used the Systematic Literature Review (SLR) method. The data collection process was carried out by screening and analyzing relevant scientific articles from 2020 to 2025 that examined the implementation of the SFAE model in Islamic Religious Education learning clusters such as Fiqh, Akidah Akhlak, and Al-Qur'an Hadith. The findings from the literature review indicate that the SFAE model has been significantly effective in boosting student learning activeness in the classroom. The transformation of students' roles into facilitators who re-explain material to their peers encourages dynamic, communicative, and collaborative learning interactions. Students have been shown to be more confident in discussions, asking questions, responding to stimuli, and presenting their thoughts. Furthermore, this increased activeness is directly proportional to strengthened motivation, self-confidence, and critical thinking skills, and has a positive impact on achieving optimal cognitive learning outcomes. Therefore, the SFAE learning model is a highly valid and effective innovative strategy for transforming Islamic Religious Education (PAI) learning environments to be more interactive, participatory, and student-centered.